The Utilization of PJJ Corners Feature to Support Academic Environment in the Field of Distance Education - Irmayati, Irmayati; Sediyaningsih, Sri; Adning, Mohamad; David, Nurpadillah (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2024)
This paper aims to provide an overview of utlisations of PJJ Corner, a feature of Universitas Terbuka’s (UT) digital library, developed through digital preservation projects to support a reading culture in the context of distance education. There are 156 digital references and 466 book collections of distance learning. This paper examines the data on the use of digital preservation in the context of distance learning in the academic context at UT. A total of 125 respondents participated in completing a questionnaire regarding digital preservation for UT's digital library. The results show that 98% of respondents already know about UT's digital library products; 80% of respondents know that there is a PJJ Corner catalog; and only 31% have accessed and utilised the PJJ Corner. Most of the access in the PJJ Corner aims to add insight related to PJJ by 33%, become a reference source by 26%, and be used for research purposes by 16%. The findings highlight the significant role of PJJ Corner in fostering reading interest and supporting academic activities, although its popularity remains lower compared to other features like Ruang Baca Virtual and UTTV. Furthermore, the PJJ Corner is making a good contribution to the development of distance learning in Indonesia through the reading activities that seek information about distance learning fields. The academic community believes that PJJ Corners can assess various reading sources online anytime and anywhere including the most recent resources and current information, as a result of the digital preservation of distance learning reference materials. Furthermore, the digital preservation of distance learning references helps them increase their reading activity for knowledge and research purposes, reference sources, and teaching materials. This study underscores the need for further promotion to enhance the utilization of PJJ Corner and the importance of digital preservation in ensuring long-term accessibility to educational materials. The results are expected to guide other institutions in developing similar initiatives to strengthen the reading culture and knowledge accessibility within academic communities.